Beyond the Scent : Analyzing the Consumer Journey in the Premium Fragrance Market - Havranová, Klaudia (2025)
This diploma thesis examines the consumer journey in the premium fragrance market in the Czech Republic and Slovakia, along with the key factors that shape it. The theoretical part introduces core concepts such as the distinctions between mass-market, premium, and luxury goods, brand equity, the marketing mix, consumer behavior, and sensory marketing. It also outlines the current state of the fragrance market in these regions, supported by specific case studies for added context. In the empirical part, a mixed-method approach was employed: qualitative expert interviews served as an exploratory stage to capture brand-side perspectives, while a quantitative consumer questionnaire delivered measurable findings from the consumer side. The research shows that the consumer journey in this segment is becoming increasingly omnichannel and non-linear, particularly among younger consumers. Although emotional aspects remain central in the branding of premium goods, functional attributes—such as scent, longevity, and price—proved to be the most decisive factors. However, statistically significant differences between consumer groups were identified, with women, for instance, placing greater emphasis on emotional and symbolic aspects, and Gen Z consumers displaying higher channel fluidity and price sensitivity.